KEMAMPUAN CORPORATE SOCIAL RESPONSIBILITY MEMODERASI PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE PADA NILAI PERUSAHAAN - Jayanti, A. A. Sagung Putri; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi, 2016)
This research aims to know the ability of corporate social responsibility to moderate the influence of good corporate social responsibility and leverage the value of the company in the real estate and property companies listed on the Indonesia stock exchange in 2011-2013. This research includes 12 real estate company and the property with the use of quantitative research in which research data is derived from the secondary data obtained from the observation of the non participant in the form of study documentation. This research data are qualified classical assumptions tests processed with multiple linear regression techniques. The results of the analysis showed that the managerial ownership and leverage the negative effect on the value of the company's institutional ownership, a positive effect on the value of the company, Corporate Social Responsibility (CSR) is not able to moderate the influence of Good Corporate Governance (GCG) and leverage the value of the company.
Keywords: GCG, Leverage, corporate values, and CSR